Ways to Increase Budget Revenues - Obidjon qizi, Baratalieva Jamila; Ismatullaevich, Soliev Ibodulloxon (European Journal of Life Safety and Stability (2660-9630), 2021)
The significance of this scientific work is that the studied and analyzed materials, opinions, conclusions and recommendations are given in the issues of improving the tax revenues of the state budget in the context of economic diversification and can be used in practice.